2001
DOI: 10.1359/jbmr.2001.16.10.1846
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Daily Treatment with Parathyroid Hormone on Bone Microarchitecture and Turnover in Patients with Osteoporosis: A Paired Biopsy Study

Abstract: We examined paired iliac crest bone biopsy specimens from patients with osteoporosis before and after treatment with daily injections of 400 U of recombinant, human parathyroid hormone 1-34 [PTH(1-34)]. Two groups of patients were studied. The first group was comprised of 8 men with an average age 49 years. They were treated with PTH for 18 months. The second group was comprised of 8 postmenopausal women with an average age 54 years. They were treated with PTH for 36 months. The women had been and were maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
353
4
13

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 600 publications
(399 citation statements)
references
References 52 publications
(60 reference statements)
29
353
4
13
Order By: Relevance
“…Results for the total hip site and the pelvis were intermediate between the spine and femoral shaft and can be explained by the mix of cortical and trabecular bone at these two ROI. An anabolic effect of teriparatide on human cortical bone was previously reported from bone biopsy studies, (13,14,16) although these were based on bone samples taken from the iliac crest and not all histology studies have shown such a pronounced effect on cortical bone. (15) There is a striking disparity between the present findings and the results of bone densitometry studies of the effects of teriparatide treatment at the spine and proximal femur.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Results for the total hip site and the pelvis were intermediate between the spine and femoral shaft and can be explained by the mix of cortical and trabecular bone at these two ROI. An anabolic effect of teriparatide on human cortical bone was previously reported from bone biopsy studies, (13,14,16) although these were based on bone samples taken from the iliac crest and not all histology studies have shown such a pronounced effect on cortical bone. (15) There is a striking disparity between the present findings and the results of bone densitometry studies of the effects of teriparatide treatment at the spine and proximal femur.…”
Section: Discussionmentioning
confidence: 94%
“…(11) Many modern treatments for osteoporosis have a profound effect on bone remodeling, and studies of bone turnover have an important role in the evaluation of their effect on bone quality. (12)(13)(14)(15)(16) Bone biopsy with double tetracycline labelling is considered the gold standard for the direct assessment of bone turnover activity, but it is complex, invasive, and costly, and restricted to a single site, the iliac crest. (13)(14)(15)(16) The most commonly used and practical method is the measurement of bone turnover markers (BTMs) in serum and urine, which have the advantage of a large and rapid response seen in patients commencing treatment for osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…PTH is a potent stimulator of bone resorption and has a biphasic effect on bone formation. There is an acute inhibition of collagen synthesis when dosed with high concentrations of PTH, but prolonged intermittent administration of this hormone produces increased bone formation, a property for which it is currently being explored clinically as an anabolic agent (Dempster, 2001) 1,25-Dihydroxy vitamin D has its greatest effect on intestinal calcium and phosphate absorption, but it also has direct effects on bone and other tissues. Vitamin D is critical for the differentiation of both osteoblasts and osteoclasts and can stimulate bone resorption and formation under some experimental conditions (Raiz, 1999).…”
Section: Systemic and Local Factors Affecting Bone Remodelingmentioning
confidence: 99%